Relationship of biological and pedagogical aspects in children’s early sports training - Abramova T.F.,; Nikitina T.M.,; Polfuntikova A.V.,; Yakutovich N.M., (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify features of the age-related development of some body systems of 6-year-old children, depending on physical activity. Methods and structure of the study. Peculiarities of age-related development were studied as a marker of the influence of various physical activities in 6-year-old children. Contingent: hockey players (41 people, training experience 1,32±0,84 years), football players (19 people, training experience 1,79±0,79 years) and untrained children (17 people). The following were studied: total dimensions and proportions of the body of the limbs, labile components of body weight; abilities: psychomotor (tests: tapping, RDO, PZMR, attention, noise immunity), cognitive (visual, verbal, spatial-logical, analytical-synthetic thinking); motor (30 m run; shuttle run 3x10 m; running with alternation 3x10 m (smooth, attached alternating, back forward); standing long jump; grip strength). Stepwise discriminant analysis was used to analyze the data. Results and conclusions. A low level of discrimination between groups of six-year-old children with different physical activity was revealed in the presence of traces of external influence, differentiating the contribution of various activity support systems to the differences between groups. The greatest difference between athletes and untrained children is inherent in cognitive development, which reflects the leading role of consciousness in the development of skills of various properties and characteristics of learning. Motor and psychomotor abilities, which differ in the manifestation of the strength of the nervous system and the quality of coordination, are consistent with the priority of the importance of the development of movement control structures in accordance with the characteristics of motor activity and learning. Morphofunctional development does not reflect the characteristics of motor activity. It is assumed that already at the very early stage of systematic sports activities, the influence of means and methods of preparation is noted, which requires taking into account the individual and age-related cognitive development of the child.